PENELITIAN FENOMENALOGI PROGRAM INTERNSHIP DI JEPANG MAHASISWA UNIVERSITAS NEGERI YOGYAKARTA TAHUN 2023 - Solikin, Moch; Akbar, Habib Maulana (Jurnal Pendidikan Vokasi Otomotif, 2024)
The background of this research is the phenomenon of the increasing interest of Yogyakarta State University (UNY) students to participate in internship programs abroad, especially in Japan, as an effort to improve global competence and international work experience for students. The purpose of this study is to describe the phenomenon of the internship selection process, during the internship, and the problems faced by students during the internship in Japan. The research method used is phenomenology with data collection through in-depth interviews with 20 students who have participated in internship programs in Japan. The data obtained were analyzed using thematic analysis techniques to identify the main themes related to the selection process, experiences, and problems faced by students. The results showed that students' experiences during the internship selection process included registration, internal selection, external selection (psychological test, interview and medical check-up) and announcement. The experience of students during internships in Japan is the improvement of Japanese language skills, adaptation of Japanese work culture and life culture, cross-country relations and cooperation, as well as soft skills and hard skills in the manufacturing industry. Problems faced by students starting from the selection of internships until completion include: selection flow that is not open, financial arrangements, internship program information, concurrent work and college time arrangements, cost information, foreign cultural differences, limited availability of housing, adaptation to 4 seasons in Japan and the short Japanese language learning before departure.